Implementasi Metode Gerakan Dalam Meningkatkan Hafalan Hadits Di SDIT Yayasan Huda Wan Nur - Wulandari, Shilvia (Mulya Literasi Publishing, 2022)
This research aims to find out the implementation of movement methods in improving hadith memorization at SDIT Huda Wan Nur Foundation. This type of research is classroom action research with a qualitative approach, with a research design in the form of a cycle that will last several cycles. The data collection techniques used are observation, tests, and documentation, and data analysis techniques, namely data reduction, data collection, and conclusion drawing. The results of this study showed that there was an improvement in memorizing hadith at SDIT Huda Wan Nur. This can be seen from the percentage results that is, in cycle I the percentage value is 55%. While in cycle II the percentage result is 95%. That way, researchers concluded that the movement method can improve the memorization of student hadith at SDIT Huda Wan Nur.